Effect of Music Therapy on Chemotherapy Nausea and Vomiting in Children with Malignancy - AS Sadat Hoseini (Tehran University of Medical Sciences, 2009)
Background & Aim: Nausea and vomiting is one of the major side-effects of chemotherapy. Due to complex nature of its management, both medical and non-medical therapies are recommended. This study aimed to investigate the effect of music therapy on chemotherapy nausea and vomiting in children with malignancy. Methods & Materials: In this quasi-experimental study, 30 children aged 8-12 who were under chemotherapy were recruited. After getting the current treatments, the children listened to a kind of music for 45 minutes at 6, 9, and 12 hours after the beginning of the chemotherapy. Nausea and vomiting was measured using both numerical and descriptive scales every 8 hours for 24 hours after beginning of the chemotherapy. Data were analyzed using Willcoxon and Mcnemar statistical tests in the SPSS, version 11.5. Results: The rate of nausea was declined significantly at the 16th and 24th hours after music therapy. Assessment of nausea by descriptive scale showed a decline only at 24th hours after music therapy. The rate of vomiting did not show any significant difference between two stages. Conclusion: Music therapy could decrease the amount of nausea in children with malignancy under chemotherapy however, it does not any effect on the rate of vomiting.